Effect of ethnicity on live birth rates after in vitro fertilisation/intracytoplasmic sperm injection treatment: analysis of UK national database - Maalouf, Walid E.; Maalouf, Wadih; Campbell, Bruce; Jayaprakasan, K. (Wiley, 2016)
Objective